2012
DOI: 10.1210/jc.2012-2303
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Studies of Nonhereditary (Sporadic) Parathyroid Adenomas

Abstract: Parathyroid adenomas typically harbor few somatic variants, consistent with their low proliferation rates. MEN1 mutation represents the major driver in sporadic parathyroid tumorigenesis although multiple low-frequency driver mutations likely account for tumors not harboring somatic MEN1 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 39 publications
7
104
0
6
Order By: Relevance
“…Additionally, it is known that both mutations occurred in a repetitive DNA sequence, consistent with a replication-slippage model of mutagenesis (18). In our series of parathyroid tumours, 8% of the cases presented somatic MEN1 mutations, which contrast with the 35% recently described by Newey et al (40). At least two factors can explain these differences: on one hand, Newey et al used whole-exome sequencing studies that can be much more sensitive, namely, detecting somatic mutations in heterogeneous tumours.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, it is known that both mutations occurred in a repetitive DNA sequence, consistent with a replication-slippage model of mutagenesis (18). In our series of parathyroid tumours, 8% of the cases presented somatic MEN1 mutations, which contrast with the 35% recently described by Newey et al (40). At least two factors can explain these differences: on one hand, Newey et al used whole-exome sequencing studies that can be much more sensitive, namely, detecting somatic mutations in heterogeneous tumours.…”
Section: Discussionsupporting
confidence: 86%
“…In patients with multiglandular pHPT, independent genetic events may be present in separate glands within the same individual (16). Previous studies have indicated that parathyroid adenomas typically harbor few somatic variants (17,18). Mutations in the MEN1 tumor suppressor gene and alterations in the CCND1 (cyclin D1/PRAD1) oncogene represent the major driver in sporadic parathyroid tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, genetic evidence argues against such a progression for parathyroid carcinoma. Genomic and genetic alterations common in benign parathyroid adenomas, most prominently loss of chromosome 11q and accompanying mutation of MEN1, which occur in 35% of parathyroid adenomas [2][3][4][5][6][7][8] , are rarely, if ever, seen in parathyroid cancer [3,4,8,9] . The clearly distinguishable patterns of genomic and genetic alterations present in parathyroid adenomas versus carcinomas suggests that parathyroid cancer most commonly arises de novo, rather than evolving from a preexisting benign adenoma [8] .…”
Section: Genetic Alterations In Parathyroid Cancermentioning
confidence: 99%